Violence Increases Psychological Distress Among Women Trafficking Survivors in Ghana - Edgemon, Timothy G. (Violence against women, 2025)
Human trafficking is a crime that is often shaped by violence, particularly for women who are trafficked. Additionally, trafficking survivors often report severe psychological distress, though research on the causes of this psychological distress is lacking, as there is little longitudinal data available on trafficking survivors. Informed by past literature on the links between violence and mental health among other traumatized groups of women, we investigate how experiences of violence influence posttraumatic stress, depression, and suicide ideation among a unique longitudinal sample of 116 labor-trafficked women in Ghana. We find that experiencing sexual violence while being trafficked is associated with higher levels of both depression and posttraumatic stress years after the trafficking period ended. This indicates both the long-term effects of stress and the enduring nature of psychological distress among the women in this study. Our analytic account of how violent experiences while trafficked impact mental health over the period of reintegration contributes to the general literature on violence and mental health among women, as well as to literature on the health implications of human trafficking.